Physical Properties, Antioxidant and Antimicrobial Activity of Chitosan Films Containing Carvacrol and Pomegranate Peel Extract - Yuan, Gaofeng; Lv, Hua; Yang, Bingjie; Chen, Xiaoe; Sun, Haiyan (Molecules (Basel, Switzerland), 2015)
Chitosan-based active films were developed by incorporation of carvacrol (10 g/L), pomegranate peel extract (PPE, 10 g/L) and carvacrol + PPE (10 g/L of each) and their physical, antioxidant and antimicrobial properties were investigated. Incorporation of carvacrol and carvacrol + PPE into the films significantly decreased the water vapor permeability, tensile strength and percentage of elongation at break. Incorporation of carvacrol, PPE and carvacrol + PPE into the films decreased the transparency, but significantly increased the total phenol content and antioxidant activity. All the films, with the exception of PPE-incorporated film, exhibited antibacterial activity against Escherichia coli and Staphylococcus aureus. In addition, the antibacterial activity against Staphylococcus aureus of the film incorporated with carvacrol + PPE was moderately higher than that incorporated with carvacrol or PPE alone, suggesting a synergistic action between carvacrol and PPE.